HUBUNGAN ANTARA PENGETAHUAN IBU POST PARTUM TENTANG MANFAAT KOLOSTRUM BAGI BAYI BARU LAHIR DENGAN PERILAKU IBU MENYUSUI DINI - Cahyono, Aris Dwi (Akademi Keperawatan Pamenang, 2013)
Colostrum is the first stage liquid milk produced at the end of pregnancy and childbirth in early (2-4 days), golden yellow or cream with a volume of 150-300 ml/day, which contains many immune substances that are needed by the infant. The purpose of this research is to know is there any correlation between mother postpartum knowledge about the benefits colostrum for the newborn baby with early breastfeeding behavior.This research used cross sectional study design. The population of 16 samples in BPS Ny. Ami Kusnan Gondang Village Plosoklaten Kediri Regency. Research was conducted on 27 March to 27 April 2011 with Accidental Sampling techniques. Data collection for independent and dependent variables mother postpartum knowledge about the benefits of colostrum for the newborn with early breastfeeding mothers behavior used questionnaire and observation checklist were analyzed descriptively used cross-tabulation.The results acquired that there respondent who have less knowledge there were 9 respondents 56% and respondent not feeding were 8 respondents (50%). It proved cross tabulatig that there was a correlation between mother postpartum knowledge about the benefits of colostrum to the mothers behavior to early breastfeeding.It can be concluded that peoples actions must be based on knowledge. So the role of nurses as educators are expected to provide to much education about the benefits colostrum for the newborn baby.Â Keywords: Knowledge, Colostrum, Breastfeeding, Mothers Behavior.